Bringing Businesswomen to a Count: A Transnational Methodological Experiment Researching Nineteenth-Century Businesswomen. Issue 2 (3rd April 2021) - Bishop, Catherine; Aston, Jennifer; van Lieshout, Carry
Abstract : This article is part of an innovative experiment to explore the influence of methodologies on the drawing of historical conclusions. Two historians researching nineteenth-century businesswomen in different places compared results. One found a preponderance of widows in business in late nineteenth-century Leeds, estimating 10 per cent of businesses were run by women. The other estimated 15–20 per cent of businesses in Sydney were run by women in the mid-nineteenth century, most by wives. Each used slightly different methods, based around trade directories. Simultaneously, a third historian's big-data analysis of the British census revealed further nuances. This article analyses the strengths and weaknesses of these methods to determine if the differences between places are real or constructed. It explores the relationship between local quantitative data and micro historical studies and how these can contribute to an international story of female economic activity.